Nitrogen inclusion in carbon nanotubes initiated by boron doping and chlorination: Their use as electrocatalysts for oxygen reduction reaction - Maboya, Winny K.; Maubane-Nkadimeng, Manoko S.; Jijana, Abongile N.; Mmako, Herry K. (Frontiers in Materials, 2022)
The use of carbon nanostructures doped with heteroatoms as electrocatalysts for oxygen reduction reaction (ORR) has attracted intense research in recent years because they are highly conductive, have good durability, and are highly electro-active. One of the strategies to modify the characteristics of carbon nanomaterials (CNMs) to render them suitable for certain applications is to dope them with boron (B) and nitrogen (N). The effect of doping CNMs with boron has been a subject of little study, and hence, it is not well understood, as compared to nitrogen doping studies. In this study, nitrogen was unintentionally doped into carbon nanotubes (CNTs) by chlorination and decomposition of triphenylborane in a catalytic vapor deposition (CVD) reactor. N-doping resulted from the use of nitrogen as a carrier gas. Microscopic and spectroscopic techniques revealed that N bonding of carbon nanostructures together with the presence of defects played pivotal roles in determining the extent of ORR performance of produced CNMs. The introduction of N in the carbon matrix during B molecule decomposition resulted in the reduction in the amount of B doped into the matrix, due to competitive incorporation of N which inhibited B introduction. The presence of pyridinic N species was responsible for a 2e− ORR performance.